Answer:12
Step-by-step explanation:
5x/6 - 2 = 8
5x/6 = 10
5x = 60
x = 12
Answer:
35.29%
Step-by-step explanation:
Just divide 30 by 85
Answer:
![x^3+5x^2+3x](https://tex.z-dn.net/?f=x%5E3%2B5x%5E2%2B3x)
Step-by-step explanation:
1) divide each term in the numerator by the term in denominator:
(remember when dividing subtract the smaller exponent from larger exponent
for example:
say a is the larger exponent, do ![x^a^-^b](https://tex.z-dn.net/?f=x%5Ea%5E-%5Eb)
x^4/x=x^3
5x^3/x=5x^2
3x^2/x=3x
so
x^3+5x^2+3x
hope this helps!
The option that is the functions is graphed below is known as option A = Y= (x+4) -2.
<h3>What is the function about?</h3>
The function graphed above is Y=|x+4|-2 because when you solve for the graphs, the number in the x-axis is always changed or turned to the other side and there one can see that it would be -4 would be +4, and +4 and also -4.
Note that
Y = (x+4) -2.
x = (0 + 4) - 2
x = 4-2
x =2
Therefore, plug x into the equation.
Y = (x+4) -2.
= ( 2 + 4) - 2
= (6) -2
= 4
Therefore, The option that is the functions is graphed below is known as option A = Y= (x+4) -2.
See full question in the image attached.
Learn more about functions from
brainly.com/question/25638609
#SPJ1